Owning the Issue Agenda: Party Strategies and Vote Choices in British Elections - Hobolt, S; Green, J (Elsevier, 2008)
Explanations of party competition and vote choice are commonly based on the Downsian view of politics: parties maximise votes by adopting positions on policy dimensions. However, recent research suggests that British voters choose parties based on evaluations of competence rather than on ideological position. This paper proposes a theoretical account which combines elements of the spatial model with the ‘issue ownership’ approach. Whereas the issue ownership theory has focused mainly on party competition, this paper examines the validity of the model from the perspective of both parties and voters, by testing its application to recent British general elections. Our findings suggest that as parties have converged ideologically, competence considerations have become more important than ideological position in British elections.